A Case of a Nonpetrous Cholesterol Granuloma Presenting as a Temporal Mass - Reeve, Nathaniel; Kahane, Jacob; Ng, Matthew (Case Reports in Otolaryngology, 2020)
Objective. A case of a skull base cholesterol granuloma (CG) of the squamosal temporal bone. This is the first ever reported case of CG in a well-pneumatized squamous temporal bone. Design. Case report and review of the literature. Discussion. CG is a cystic mass typically found in the petrous apex and occasionally in the paranasal sinuses and orbit. Experience with the treatment of these expansile and inflammatory processes has largely been garnered from those occurring in the petrous apex, where they are surgically drained, via a transtympanic, transmastoid, or middle fossa approach. We report a case of cholesterol granuloma situated in the temporal fossa presenting as a temporal mass. The accessible location of this particular lesion made it amenable to total excision, avoiding the need for surgical drainage and possibility for recurrence. Conclusion. This case supports the theory of pathogenesis of such lesions typically occurring where pneumatized air spaces interface with bone marrow, in this case, where the reaches of pneumatized cells in the squamous portion of the temporal bone meet diploic bone.